The Causality Nexus Between the Tako-tsubo Syndrome and an Assault: A Forensic Case Report. (September 2018) - Zribi, Malek; Manoubi, Syrine Azza; Karray, Narjes; Charfeddine, Salma; Benamar, Wiem; Hammami, Zouhir; Kammoun, Samir; Maatoug, Samir
Abstract : Abstract: "Tako-tsubo" cardiomyopathy, also known as "broken heart syndrome, " is one of the rarest types of stress-induced cardiomyopathy. It frequently mimics acute coronary syndrome, characterized by transient left ventricular dysfunction, electrocardiographic changes, and release of myocardial enzymes. After treatment, the patients are cured in most cases without sequelae. Tako-tsubo syndrome is rarely considered as a reason for consultation in the forensic department. Herein, we report a case of a 68-year-old woman who was assaulted by her police officer neighbor. The latter punched her in the arms and kneed her in the gut without causing any intrathoracic or abdominal injury. The victim was urgently hospitalized in the cardiology department for chest pain and dyspnea accompanied by ST-segment elevation and high troponin level. Tako-tsubo cardiomyopathy diagnosis was based on clinical findings, echocardiography, coronary angiography, and magnetic resonance imaging findings. A forensic medicine consult was initially solicited for the drafting of an initial medical certificate and for evaluating the total transitory disability rate. A second consultation was then sought to evaluate the permanent partial disability. We report this work to discuss the conduct of the forensic pathologist and to prove the causality relationship between the assault and the physical injuries.